Effectiveness of trospium chloride and doxazosin mesylate combination in neurogenic bladder patients with spinal cord injury - Kulaklı, Fazıl; Köklü, Kurtuluş; Ersöz, Murat; Özişler, Zuhal; Çulha, Canan; Özel, Sumru (The European Research Journal, 2018)
Objective. The aim of this study was to compare the effects of trospium chloride (TCL) and TCL + doxazosin (DXZ) combination to bladder capacity and residual urine volume (RUV) in spinal cord injury (SCI) patients with neurogenic bladder. Methods. The study included 120 patients with SCI. Urodynamic data of patients were reviewed retrospectively. Changes in maximum cystometric capacity (MCC) as well as RUV were determined in patients using 60-90 mg/day TCL (Group 1, n = 98) or 60-90 mg/day TCL + 4-6 mg/day DXZ (Group 2, n = 22). Results. There was statistically significant increase in both MCC and RUV values in both groups. There was no statistical difference in MCC and RUV values in Group 1 and Group 2 (p = 0.111 and p = 0.664, respectively). There was a significant weak negative correlation between duration of injury and MCC values (r = 0.185; p = 0.043), meaning as the duration of injury increased, MCC decreased. There was no statistically significant correlation between medication usage duration with MCC and RUV (r = -0.129; p = 0.159 and r = -0.68; p = 0.462, respectively). Conclusions. Anticholinergic treatment is currently the mainstay conservative treatment of neurogenic detrusor overactivity. The impact of alfa blockers on neurogenic bladder has been less well evaluated. We consider that, adding DXZ to TCL has no additional benefit to increase bladder capacity and reduce RUV. Further studies are needed to determine the location of DXZ treatment in SCI patients with neurogenic bladder.